Financial Innovations and Its Effects on Economic System - Jiacheng Lyu; Yingbo Lyu; Wenbo Lyu (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
In recent years, as China’s economy has transitioned from a high-speed growth phase to a high-quality development phase, financial innovation has been recognized as one of the key drivers for economic advancement. The 19th National Congress of the Communist Party of China (CPC) outlined crucial strategies for promoting high-quality economic development, with financial innovation being regarded as a pivotal means to achieve this objective. Against this backdrop, conducting in-depth research on the impact of financial innovation within the financial system on economic advancement is of significant importance. In China, financial innovation has emerged as a critical driving force for promoting economic development and enhancing economic quality. The Chinese government actively promotes financial reform and innovation, striving to build a more open, transparent, and robust financial system to enhance the capacity of financial services for the real economy. This effort aims to accelerate the transformation of the economic development model and achieve high-quality economic development. Nevertheless, the mechanisms through which financial innovation impacts the economy remain not fully understood, necessitating further investigation. This study aims to systematically review and empirically analyze the impact of financial innovation on China’s high-quality economic development. Through this research, the theoretical foundations and decision-making support were provided to guide financial innovation, expedite the construction of a financially strong nation, and promote high-quality development. This paper identifies the positive impact and important role of financial innovation on economic growth and puts forward relevant suggestions to decision-makers.